Detection of clinically significant cancer in the anterior prostate by transperineal biopsy. (4th August 2020) - Cowan, Tim; Baker, Emily; McCray, Gabriella; Reeves, Fairleigh; Houlihan, Kimberley; Johns‐Putra, Lydia
Abstract : Objective: To determine the incidence of clinically significant prostate cancer (csPCa) detected exclusively in the anterior prostate using transperineal prostate biopsy. Patients and Methods: Histopathology results of all patients who underwent transperineal prostate biopsy between February 2016 and March 2018 at a single institution were assessed for distribution of cancer within the prostate. Patients with cancer found exclusively in the anterior prostate were then compared to those with any cancer found in the posterior or lateral prostate with International Society of Urological Pathology Grade Group 2–5 cancers being considered csPCa. Results: A total of 508 patients were included. Overall, 12.0% of the cohort had csPCa detected only in anterior biopsies. When stratified by prostate‐specific antigen (PSA) level, 6.6% of men with a PSA level of 4.1–10.0 ng/mL and 8.2% of men with a PSA level of >10.0 ng/mL had csPCa detected in the anterior prostate alone. Conclusion: Transperineal biopsy has the ability to diagnose anteriorly located csPCa that would potentially have been missed by the transrectal approach.